La desigualdad en la adopción de niños, niñas y adolescentes en el Ecuador cuando los solicitantes son familias monoparentales - Maza Macas, Josselyn Elizabeth (2023)
The research work titled “The inequality in the adoption of boys, girls and youth in Ecuador when the applicants are single parent”. It is known the adoption has as a finality, restitute a right for boys, girls, and youths to have a family, which is created a link of filiation between a younger in orphan status and the adoption family. The organic code of the children and teenagers establishes the process to follow and the requirenments that must accomplish to adopt; however, into the beginning of the adoption. It is established an unequal and discriminary treat, so that it is prioritized the adoption for the heterosexual and couples legally constituted, about the adoption as these lonely people, this beginning place to the single parents in low level, let them as the last alternative. The researching work looking for determine. How is important to remove the priority of the adoptant couples, because it affects to two groups of people which are: boys, girls and youth considered as vulnerable group, in that way it is injured its high interests to formed a family because continue in to be adopted, and unequal way it is damaged to those people who without any necesity of a couple wants to convert in father and mother, doing to go across a large and complex process. In the researched work it was applied materials and methods which let to develop the researching; futhermore, it was done interviews and surveys to professionals of law, which the results obtained served to plan the propose of the legal reform of the Organic code of children and youths with the finality to eliminate the priority given to applicant couples into the adoption process.